A perspective on household dairy farming in district Naushahro Feroze, Sindh Pakistan - Israr Yasin; Talha; Hira; Warisha; Sajid Hussain (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
A household (HHs) survey was conducted to collect the information on household dairy farming with special reference to management of livestock, milk production and marketing as well as role of livestock in household income in Naushahro Feroze district of Sindh Province of Pakistan. Six hundred households were selected from 40 villages in four out of nine Talukas (administrative units) using multistage clustering method. Estimates of the study revealed that 54% of the households possessed buffaloes. Average number of buffaloes was estimated at 4.28 while 376 (63%) of the household reported cattle with average number of 4.38 heads per household.